PENINGKATAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK SMP MELALUI MODEL PEMBELAJARAN SAVI DAN MENGONTROL DISIPLIN BELAJAR - I Made Surat (LP3M Universitas PGRI Mahadewa Indonesia, 2020)
The main objective of this study was to determine the effect of the SAVI learning model on mathematics learning outcomes by controlling the learning discipline of class VIII students at SMPN11 Denpasar. This type of research is classified as a quasi-experimental (quasi-experimental) design with a non-equivalent posstest only control group design. The population in this study were all students of class VIII at SMP N11 Denpasar which consisted of 7 classes. So class VIII D as the experimental class and class VIII A as the control class with many students for each class of 39 students who were taken by multi stage random sampling technique. The instruments used in collecting data were tests to measure mathematics learning outcomes and questionnaires to measure students' discipline in learning mathematics. Data were analyzed using t-test and one-way ANACOVA. The results of this study indicate the following, (1) there is a significant influence on the mathematics learning outcomes of students using the SAVI learning model with the mathematics learning outcomes of students using conventional learning models with the found price (tcount> ttable or 5.331> 1.665). (2) After controlling the discipline of learning there is an effect of mathematics learning outcomes between those using the SAVI learning model and mathematics learning outcomes using conventional learning models and the price is found (Fcount> Ftable or 31.05> 3.97). The conclusion from this research is that there is an effect of the SAVI learning model on mathematics learning outcomes after controlling the discipline of learning of class VIII students of SMP N 11 Denpasar.